The infoproduct consumer behavior (Research, Society and Development, 2021)
The modern consumer behavior has been changing quickly since the internet boom in the 2000s. If at that time the change of a whole culture of humanity was already announced with the advent of the web, with social networks this consumer has become even more active in the process and aware of its power. The objective of this work is to analyze the behavior of this consumer of digital products and for that, we used bibliographical and documentary research on the subject. This is a subject in constant transformation and, consequently, there is still much to be observed, as technology is also constantly evolving. What can be seen from the literature on the subject, as well as documentary research, is that the traditional consumer has changed his behavior and tries to adapt to digital consumption given the range of offers that this new format offers. On the other hand, the market evolves to meet the increasingly demanding needs of the consumer.